Living in symbiosis with COVID: two delayed presentations of soft tissue infections in elderly patients with COVID-19 infection - Gratsianskiy, Denis; Kiarie, Patrick K.; Baek, Inhae; Liguori, Tyler; Nikolov, Nicole K.; Louis, Martine A.; Mandava, Neil (International Surgery Journal, 2024)
Retroperitoneal and extensive breast abscesses in elderly patients are associated with a significant burden of comorbidities, insidious symptoms, and signs resulting in delayed diagnosis. We present two elderly COVID-19-positive patients with retroperitoneal and breast abscesses. Both patients underwent multiple procedures and , despite a protracted course, survived each two potentially lethal infections. A 72-year-old man presented to the emergency department (ED) with back pain. Labs showed a polymerase chain reaction (PCR)-positive COVID-19 test and leukocytosis. A computed tomography scan of the abdomen and pelvis (CTAP) showed a perirectal abscess spreading into the pelvis and retroperitoneum. The patient underwent an incision and drainage (I and D). Additional imaging found multiple collections with extension into the retroperitoneum. These were drained, and the patient was discharged after repeat imaging showed resolution. A 78-year-old female was admitted with swelling of the right breast. Labs showed a positive PCR COVID-19 test, and chest computed tomography (CT) showed a rim-enhancing collection extending from the right breast into the right pectoralis muscle. The patient was started on antibiotics and underwent an I and D of the right breast. She was discharged on post-operative day (POD) four on antibiotics. She was readmitted 32 days later with a left sided abscess overlying the left pectoralis and was successfully treated conservatively with a course of antibiotics. There are few studies on the formation of abscesses in the breast and retroperitoneum in the setting of COVID-19 infection. Thus, information on the topic can aid physicians in maintaining clinical suspicion of severe abscesses illness in elderly patients presenting with vague clinical symptoms or symptoms concerning soft-tissue infections in the setting of COVID-19 infections